Vascular Myelopathies - Moftakhar, Parham; Hetts, Steven W.; Ko, Nerissa U. (Seminars in Neurology, 2012)
Vascular abnormalities of the spinal cord are an important cause of myelopathy. Clinicians need to be aware of these disorders as they can present with a variety of neurologic symptoms ranging from acute spinal neurologic emergencies, relapsing/remitting spells to gradually progressive dysfunction. The unique topography and vascular anatomy of the spinal cord lends to the variety of clinical presentations. Both ischemic and hemorrhagic insults can occur. Increased clinical suspicion, better detection with newer imaging modalities and early treatment can often impact outcomes. The authors review clinical diagnoses, novel imaging, and advanced treatment modalities for the most common causes of vascular myelopathy.
Keywords: spinal cord; arteriovenous malformation; dural fistula; cavernoma; myelopathy